'ASMR' autobiographies and the (life-)writing of digital subjectivity. (April 2019) - Gallagher, Rob
For years now, a growing online subculture has been exchanging videos designed to induce 'autonomous sensory meridian response' (ASMR), a mysterious, blissfully relaxing tingling sensation held to alleviate anxiety, pain, insomnia and depression. Emerging from online health forums, ASMR culture today centres on YouTube, where 'ASMRtists' have used the feedback mechanisms built into social media platforms to refine a repertoire of 'trigger' techniques. Exemplifying a wider trend for using 'ambient media' as mood modulators and task facilitators (Roquet, 2016 Ambient Media: Japanese Atmospheres of Self . London: University of Minnesota Press.), ASMR culture's use of the word 'trigger' is telling, gesturing towards what Halberstam ((2014) You Are Triggering Me! The Neo-Liberal Rhetoric of Harm, Danger and Trauma. Bully Bloggers . Available at:https://bullybloggers.wordpress.com/2014/07/05/you-are-triggering-me-the-neo-liberal-rhetoric-of-harm-danger-and-trauma/ (accessed 8 August 2018)) sees as a shift away from the Freudian notion of 'memory as a palimpsest' towards one of memory as 'a live wire sitting in the psyche waiting for a spark', whereby digital subjects become black-boxed nodes in a cybernetic circuit. This shift has serious implications for the humanities and is particularly resonant for scholars of life-writing. As McNeill ((2012) There is no "I" in network: Social networks sites and posthuman auto/biography. Biography 35(1): 65–82.) argues, digital technologies 'complicate[] definitions of the self and its boundaries, both dismantling and sustaining the humanist subject in practices of personal narrative' (p. 65). The resulting friction is highlighted in 'ASMR autobiographies': texts narrating the author's experiences of ASMR and their discovery of online ASMR communities. Echoing familiar auto/biographical forms, from medical case histories and coming out narratives to tales of religious conversion, these texts show that the models of subjectivity we have inherited from Enlightenment philosophy, religion, psychology and Romantic literature retain some cultural purchase. But they also suggest digital media are fostering new understandings of personhood informed by cybernetics, evolutionary psychology, behaviourism and neuroscience. Focusing on works by Andrew MacMuiris, Andrea Seigel and Jon Kersey while also addressing a range of other texts, this article asks what ASMR autobiographies can tell us about digital subjectivity.